Impact of vitamin D3 supplementation on motor functionality and the immune response in Parkinson’s disease patients with vitamin D deficiency - Danfeng Li; Xibo Ma; Wentao Zhang; Ping Zhong; Mei Li; Shihua Liu (Scientific Reports)
Abstract Parkinson’s disease (PD) patients frequently exhibit vitamin D deficiency and an imbalance in T helper 17 (Th17) and regulatory T (Treg) cells, which may contribute to disease pathogenesis. Preclinical evidence suggests vitamin D regulates Th17/Treg balance, but the therapeutic effects of supplementation in PD remain unestablished. This randomized controlled trial investigated peripheral blood levels of vitamin D, Treg, and Th17 cells in PD patients, examined their associations with clinical outcomes, and assessed vitamin D3 supplementation’s effects on immunological and motor functions. In this randomized, double-blind, placebo-controlled trial, 51 PD patients and 50 healthy controls (HCs) were enrolled. Thirty PD patients with vitamin D deficiency were randomized to receive vitamin D3 (n = 15) or placebo (vegetable oil, n = 15) for three months. Serum 25(OH)D3 levels were measured by electrochemiluminescence, and Th17/Treg cells were analyzed by flow cytometry. Motor and non-motor symptoms were assessed using standardized scales. Vitamin D3 supplementation significantly increased 25(OH)D3 levels (p < 0.05), reduced Th17 cells (4.62 ± 1.09 to 3.25 ± 1.14, p = 0.003), and elevated Tregs (3.25 ± 0.90 to 4.52 ± 0.95, p = 0.003). Motor function (UPDRS and UPDRS-III) improved in the vitamin D3 group (p < 0.001), while no changes were observed in the placebo group. This preliminary study suggests that vitamin D3 supplementation may restore Th17/Treg balance and potentially alleviate motor symptoms in vitamin D-deficient PD patients, indicating a possible therapeutic strategy. Trial registration: ClinicalTrials.gov: NCT:06539260. Registered 05 August 2024 - Retrospectively registered, https://clinicaltrials.gov/study/NCT06539260 .